1981
DOI: 10.1111/j.1365-2494.1981.tb01569.x
|View full text |Cite
|
Sign up to set email alerts
|

Silage and milk production: a comparison between barley and dried sugar‐beet pulp as silage supplements

Abstract: Two grass silages made from perennial ryegrass, and with D-values of 0-616 and 0-655, were offered ad libitum to 18 Ayrshire cows in two feeding experiments. On the control treatment the silages were supplemented with soybean meal only, and on the other two treatments with equal weights of DM from either barley or dried molassed sugar-beet pulp plus the same weight of soya as on the control treatment. The daily intakes of silage DM were not significantly different on the barley and beet-pulp treatments, and, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
18
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 11 publications
13
18
1
Order By: Relevance
“…Rumen VFA was not measured in the present study, but Murphy et al (1986) found a decrease in this ratio from 5.2 to 4.5 in dairy cows when 670 g/kg of Ba was replaced by SBP. The results of Castle (1972) indicate a similar trend, and Castle noted as well a lower fat content on SBP diet than on Ba diet. In these studies, the major changes in rumen VFA proportions included an increase in propionate and a decrease in butyrate on SBP diets.…”
Section: Production Responsesupporting
confidence: 70%
See 3 more Smart Citations
“…Rumen VFA was not measured in the present study, but Murphy et al (1986) found a decrease in this ratio from 5.2 to 4.5 in dairy cows when 670 g/kg of Ba was replaced by SBP. The results of Castle (1972) indicate a similar trend, and Castle noted as well a lower fat content on SBP diet than on Ba diet. In these studies, the major changes in rumen VFA proportions included an increase in propionate and a decrease in butyrate on SBP diets.…”
Section: Production Responsesupporting
confidence: 70%
“…A similar increase in milk yield was also recorded by Thomas et al (1986) when Ba supplement was replaced by a mixture of SBP, extracted rice bran and fat prills. However, Mayne and Gordon (1984) Castle et al 1981) there were no statistically significant differences in milk production between Ba and SBP supplements, although in most studies the milk yield was slightly higher when SBP diets were given. In grazing cows the milk yield was higher when Ba was replaced by SBP (Murphy 1985), or more generally, starchy concentrate by fibrous concentrate (Meus 1986).…”
Section: Production Responsementioning
confidence: 91%
See 2 more Smart Citations
“…In the previous trial (Huhtanen et al 1988), increasing the proportion of barley fibre in the diet increased silage DM intake markedly but the effect was mainly offset by the reduced intake of supplement. Likewise, when small or moderate levels of concentrate have been used, the effect of concentrate energy source on silage DM intake has been relatively small (Castle et al 1981, Mayne and Gordon 1984, Sloan et al 1987, Huhtanen 1987. On the other hand, Thomas et al (1986) reported that cows given high levels of supplement based on unmolassed sugar beet pulp and rice bran ate 0.9 kg/day more silage DM than those given barley based supplements.…”
Section: Discussionmentioning
confidence: 99%